Impact of systems biology on metabolic engineering - Nielsen, Jens (Henry Stewart Talks, 2014)
The biorefinery concept, The process of metabolic engineering (ME), Approaches in systems biology (SB), Genome scale metabolic models (GEMs), Using SB to design succinic acid production in yeast, Using SB to compare metabolism of yeast strains, Using SB to compare penicillin producing in yeast strains, Inverse metabolic engineering, Using inverse ME to improve galactose utilization in yeast, Mechanisms of evolutionary trade-offs
Reviewed at 2021/11/11